Income risk, precautionary saving, and loss aversion: An empirical test - Marcela Ibanez; Sebastian O. Schneider (Max Planck Institute for Research on Collective Goods, 2023)
This paper empirically examines the behavioral precautionary saving hypothesis that uncertainty about future income triggers an increase in saving because of loss aversion. Guided by the theoretical model of Koszegi and Rabin (2009), we first extend their theoretical analysis to also consider the internal margin, i.e., the strength, of loss aversion, and then empirically study the relation between income risk, experimentally elicited loss aversion, and precautionary savings. We do so using a sample of 640 individuals from the low-income population of Bogotá, characterized by limited financial education and subject to substantial income risk. In line with the theoretical predictions, we find that an increase in income risk is associated with higher savings for loss-averse individuals, and that this increase in savings grows with the degree of loss aversion. An accompanying laboratory experiment confirms that an exogenous increase in income risk causally leads to this observed pattern. Thus, consistent with the theoretical predictions derived from the model of Koszegi and Rabin (2009), but in contrast to common assumptions, our findings establish that loss aversion is not necessarily an obstacle to saving, and thus identify new approaches of increasing saving among individuals with low financial education.
hdl:21.11116/0000-000D-5CFF-E
Keywords: D11; D14; D15; D81; D90; G40; J65; O16; 330; Reference-dependent utility; expectations; consumption plans; precautionary savings; loss aversion; risk preferences; income risk; low income; Bogotá; experiment